Comparison of the salt resistance of Solanum lycopersicum x Solanum chilense hybrids and their parents - Bigot, Servane; Leclef, Claire; Rosales, Camila; Martínez, Juan-Pablo; Lutts, Stanley; Quinet, Muriel (Frontiers in Horticulture, 2023)
Soil salinization is a major global problem. Tomato (Solanum lycopersicum) is one of the main crops produced in the world and is cultivated in areas affected by salinity. However, it is considered as a glycophyte species and is sensitive to salt stress. Solanum chilense is a wild tomato native to the Atacama Desert and is therefore adapted to harsh environmental conditions, including salinity. It is considered as a promising source of genes for tomato improvement. However, the physiology of abiotic stress resistance remains largely unknown in S. chilense and no studies have investigated the resistance of S. lycopersicum x S. chilense interspecific hybrids and the potential value of their use in harsh environments. In this study, we compared the salt resistance of S. lycopersicum, S. chilense and their hybrids at vegetative and reproductive stages. Overall, hybrids showed an intermediate behavior between their parents and a higher salt resistance than S. lycopersicum. Their physiological behavior toward salt stress was sometimes closed to S. lycopersicum and sometimes closed to S. chilense. Their sodium accumulation was intermediate between parents, with a sodium concentration closer to S. lycopersicum than S. chilense in roots, but with an aerial concentration closer to S. chilense than to S. lycopersicum. In inflorescences and fruits, the sodium concentration of hybrids was closer to S. lycopersicum than to S. chilense. Despite a decrease in instantaneous transpiration, the photosynthetic nitrogen use efficiency of hybrids was not decreased by salt stress: our results suggest a greater tolerance to the osmotic phase of salt stress in hybrids compared to the parents. Regarding the reproductive stage, inflorescence production and fruit quality were not affected by salt in hybrids. This study highlights the potential use of hybrids in improving tomato for salt stress resistance.